Influence of gender portrayal in Disney cartoons on young female audiences / Ahmad Adnin Zidane Muslim... [et al.] - Muslim, Ahmad Adnin Zidane; Kamarol Zaman, Dhiya Zahiah; Ghazali, Farahanis; Fletcher, Maegan Selena Anne; Nik Zaid, Nik Nur Najla; Eligius, Rosa (Faculty of Communication & Media Studies, 2020)
Gender roles are built on different prospects that individuals, groups, and societies have of individuals based on their sex as well as each society's values and principles about gender. Gender roles are the product of the interactions between individuals and their environments, and they give individuals cues about what sort of behaviour is believed to be appropriate for what sex. However, there are some problems in this research. To name a few, females are greatly underrepresented in cartoons, often greatly stereotyped as damsels in distress that need a prince charming to save them and the mentality that women are weaker than men, dependent, beautiful which attracts male as a sex object. The researchers used a qualitative research method. The researchers agreed to do an interview with young female informants in order to identify the influence of gender portrayal in Disney cartoons and how their perception is shaped. To sum up, the researchers found that some of Disney's princess described that females should not follow out there in real life. Disney Princesses have grown into many different storylines and characteristics, it shows they are the type that kids should follow and how a female should be. Lastly, all informants are well aware of how females are depicted in Disney movies and that it is a growing problem that needs to be attended to.